Athenry Dominican Priory, south nave wall, niche, capital - O'Donovan, Danielle (My University, 2008)
Capital of middle niche/sedilia of south nave wall, moulding from top down comprises: chamfer, fillet, hollow, stiff-leaf foliage, bell, necking roll-and-fillet. Here again Early English characteristics are manifest but the niche may date from the later middle ages.
Niche
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Gothic capitals (Architecture); Late Medieval; roll-and-fillet moldings; bell capitals